Student growth measures: What we've been missing. (December 2019) - Watson, Michael
The move toward assessments that measure student growth, rather than just proficiency, has been perceived as an improvement in state accountability systems. However, Michael Watson explains that, for many students, these measures present an incomplete picture. Because they are based on grade-level assessments, any growth achieved by students who are above or below grade level is lost. He recommends the use of adaptive assessments that incorporate material from multiple grade levels .